Comparative Study of Mobile Robot Control on Android Smartphone Based on Wireless Technology - Bobi Kurniawan (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2017)
In this study, designing an application on Android smartphone that serves as a remote control that can control the movement of a robot car. The car robot uses two communications media namely Bluetooth and WiFi and also two types of input commands namely screen button and accelerometer. Both communication media and input commands will be compiled to be able to determine the most appropriate control. As for the results of the analysis and testing, has been obtained the percentage of success input screenplay command 95.84% and accelerometer 91.20%. While the Bluetooth communication media has a percentage of success of 95.72% and WiFi 91.32%